Drug Design Novel Advances in the Omics Field and Applications - Aditya Parikesit, Arli (IntechOpen, 2021)
Right before the COVID-19 pandemic declared by the World Health Organization (WHO), life sciences have incited novel areas of studies that revolutionize the health sector. They are the studies of structural bioinformatics, pharmacogenomics, and metabolomics. The structural bioinformatics field is the very foundation of drug design research, as it provides insight into the molecular simulations and interactions between the biomolecules and the drug candidates. Secondly, pharmacogenomics is the starting point of any efforts in developing personalized medicine. Lastly, metabolomics provides instrumentation to elicit biomarkers for various diseases and health conditions. These studies have enabled current accelerated effort in COVID-19 research, as well as other communicable and non-communicable diseases.